Global divergence in the de-routinization of jobs - Piotr Lewandowski; Albert Park; Simone Schotte (Asian Development Bank (ADB), 2023)
This study introduces a methodology to estimate the economy-specific task content of occupations across economies at different income levels. Combining these with employment data in 87 economies, the results show that occupations in low- and middle-income economies are more routine-intensive than in high-income economies, which is attributed to lower technology use in less-developed economies. Non-routine work continues to dominate in high-income economies while routine work remains in low-income and middle-income economies. These findings, using economy-specific estimates of occupational task content, contradict the assumption based on conventional measures that task content of occupations is converging globally. The finding of divergent trends in the relative routine intensity of work in developed and developing economies has important policy implications. Investment in skills, technology use, and participation in global value chains are key factors for work content and productivity to converge with those in high-income economies. The assumption that occupations are converging globally may also overestimate the role of routine-replacing technological change in explaining wage inequality in low- or middle-income economies.
Keywords: J24; J31; O14; O15; 330; occupational task content; routine-task intensity; skills; jobs divergence; wage inequality